2014
DOI: 10.1111/jdv.12455
|View full text |Cite
|
Sign up to set email alerts
|

Rhodotorula mucilaginosa skin infection in a patient treated with sorafenib

Abstract: of the species is R. mucilaginosa; it is a ubiquitous pathogen isolated from many sources such as shower curtains, bathtubs, tooth brushes and medical equipments. Before 1985, Rhodotorula was not considered yet as a pathogen, but today it is known to cause significant infections in immunocompromised patients, usually with a malignancy or immunosuppression. Fungemia associated with central venous catheter is the most common consequence of R. mucilaginosa, followed by eye infection (keratitis and endophthalmitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…No additional studies were found by hand‐screening of the included articles’ references. Finally, 111 met the criteria . Additional information was kindly provided by the corresponding author of one study .…”
Section: Resultsmentioning
confidence: 99%
“…No additional studies were found by hand‐screening of the included articles’ references. Finally, 111 met the criteria . Additional information was kindly provided by the corresponding author of one study .…”
Section: Resultsmentioning
confidence: 99%
“…5 Other cases of cutaneous Rhodotorula infection have been reported. 2,3 Our patient is unusual as his infection presented over 30 years post-transplant. It is likely that Rhodotorula was acquired when he recommenced haemodialysis, possibly due to his elbow injury or his central venous catheters.…”
Section: Reportmentioning
confidence: 84%
“…Rhodotorula was originally not considered pathogenic, but since the mid‐1980s, infections have been increasingly recognized, possibly because of increasing use of central venous catheters or previous diagnostic difficulties. Rhodotorula infections most frequently present as fungaemia, related to central venous catheters, but ocular infection, meningitis, onychomycosis and peritonitis also occur …”
Section: Reportmentioning
confidence: 99%
See 2 more Smart Citations